You are on page 1of 4

Show that (p ∧ q) → (p ∨ q) is a tautology?

Ask Question

up vote14down vote favorite

2
I am having a little trouble understanding proofs without truth tables particularly when it comes to →

Here is a problem I am confused with:

Show that (p ∧ q) → (p ∨ q) is a tautology

The first step shows: (p ∧ q) → (p ∨ q) ≡ ¬(p ∧ q) ∨ (p ∨ q)

I've been reading my text book and looking at Equivalence Laws. I know the answer to this but I don't understand the first step.

How is (p ∧ q)→ ≡ ¬(p ∧ q)?

If someone could explain this I would be extremely grateful. I'm sure its something simple and I am overlooking it.

The first thing I want to do when seeing this is


(p ∧ q) → (p ∨ q) ≡ ¬(p → ¬q)→(p ∨ q)

but the answer shows:


¬ (p ∧ q) ∨ (p ∨ q) (by logical equivalence)

I don't see a equivalence law that explains this.

discrete-mathematics logic propositional-calculus

shareciteimprove this question


edited Mar 7 '16 at 19:00

nc4pk
1033
asked Mar 7 '16 at 1:09

Danny
76114

 It seems pretty obvious to me, the negation of the conclusion is ¬p∧¬q¬p∧¬q which clearly falsifies the hypothesis.– Jared Mar 7 '16 at 1:21
 Another question about the same formula: math.stackexchange.com/questions/275689/… – Martin SleziakMar 7 '16 at 9:15
 What does "T.T." in the middle of your question mean? – TRiG Mar 7 '16 at 16:14
 2
@TRiG - I'm pretty sure it's just a tearful face emoticon. – Malice Vidrine Mar 7 '16 at 17:01
add a comment
8 Answers
activeoldestvotes

up vote19down vote accepted

It is because of the following equivalence law, which you can prove from a truth table:

r→s≡¬r∨s.r→s≡¬r∨s.

If you let r=p∧qr=p∧q and s=p∨qs=p∨q, you get what you are looking for, namely that
(p∧q)→(p∨q)≡¬(p∧q)∨(p∨q).(p∧q)→(p∨q)≡¬(p∧q)∨(p∨q).

shareciteimprove this answer


answered Mar 7 '16 at 1:15
Mankind
9,94172242

 1
Thank you! I was unaware you could do it like that. – Danny Mar 7 '16 at 1:26
add a comment
up vote19down vote
This is a classic equivalence

p→q≡¬p∨q.(1)(1)p→q≡¬p∨q.

We can examine equivalence using a truth table

pTTFFqTFTF¬pFFTTp→qTFTT¬p∨qTFTTpq¬pp→q¬p∨qTTFTTTFFFFFTTTTFFTTT

Hence, p→q≡¬p∨qp→q≡¬p∨q.
Further, if a≡p∧qa≡p∧q and b≡p∨qb≡p∨q, and so
a→b≡¬a∨b≡¬(p∧q)∨(p∨q)≡(¬p∨¬q)∨(p∨q),a→b≡¬a∨b≡¬(p∧q)∨(p∨q)≡(¬p∨¬q)∨(p∨q),

by using (1)(1).
shareciteimprove this answer
edited Mar 7 '16 at 1:27
answered Mar 7 '16 at 1:17

Em.
14.8k71937
add a comment
up vote7down vote
To show (p ∧ q) → (p ∨ q).

If (p ∧ q) is true, then both p and q are true, so (p ∨ q) is true, and T→TT→T is true.
If (p ∧ q) is false, then (p ∧ q) → (p ∨ q) is true, because false implies anything.

Q.E.D.

shareciteimprove this answer


answered Mar 7 '16 at 2:47

marty cohen
69.1k446122

 1
True, but doesn't address what seems to be the main question. – Carl Witthoft Mar 7 '16 at 21:01
add a comment
up vote5down vote
I know you asked specifically about a given proof, but here is another way:

(1) Assume p ∧ q

(2) By ∧-elimination, p

(3) By ∨-introduction, p ∨ q

(4) By →-introduction and marking the assumption (1), (p ∧ q) → (p ∨ q).


In less formal language: if P and Q is true, then you can look at either P or Q separately and it must be true. Now from any true statement you can
create a longer true statement by creating a disjunction with any statement: if P is true, then "P or R" is also true for any statement R (e.g. if you
are sure "it is raining", then it is also the case that "it is raining or you are a dragon"). In particular taking R = Q in this case allows you to reason
that P or Q is true.
shareciteimprove this answer
edited Mar 7 '16 at 16:42
answered Mar 7 '16 at 11:05

CompuChip
58426
add a comment
up vote2down vote
Combine your first step with De Morgan's Law:
(p∧q)→(p∨q)≡≡≡≡≡¬(p∧q)∨(p∨q)(¬p∨¬q)∨(p∨q)(¬p∨p)∨(¬q∨q)T∨TTDefinition of →De Morgan's LawAssociativity and
commutativity of ∨(p∧q)→(p∨q)≡¬(p∧q)∨(p∨q)Definition of →≡(¬p∨¬q)∨(p∨q)De Morgan's Law≡(¬p∨p)∨(¬q∨q)Associativity and
commutativity of ∨≡T∨T≡T

shareciteimprove this answer


answered Mar 7 '16 at 16:25

chepner
40327
add a comment
up vote2down vote
Alternately:

p ∧ q Assumed <--------\
p base Extract P ∧ Q ⊢ P |
p ∨ q base Widening P ⊢ P ∨ Q |
(p∧q)→(p∨q) pop assumption -/
This isn't quite rendering right -- need a fixed width font.

shareciteimprove this answer


answered Mar 7 '16 at 17:24

Joshua
30729
add a comment
up vote1down vote
As ¬p∨p¬p∨p is trivial and p→qp→q means pp necessitates qq. This gives ¬p∨q¬p∨q.
shareciteimprove this answer
answered Mar 7 '16 at 1:49

Mathlover
3,4231021
add a comment
up vote1down vote
The following is an inference rule approach to showing that P→Q≡¬P∨QP→Q≡¬P∨Q, using the Constructive Dillema inference rule:
P→Q, R→S, P∨RQ∨SP→Q, R→S, P∨RQ∨S
It can be shown that ¬P∨P¬P∨P and ¬P→¬P¬P→¬P are tautologies, and given that we know P→QP→Q , we can substitute into the above
inference rule.
¬P→¬P, P→Q, ¬P∨P¬P∨Q¬P→¬P, P→Q, ¬P∨P¬P∨Q

So far we have shown that (P→Q) ⊢(¬P∨Q)(P→Q) ⊢(¬P∨Q). To finish proving the equivalency P→Q≡¬P∨Q P→Q≡¬P∨Q we also need to
show (¬P∨Q)⊢(¬P∨Q)(¬P∨Q)⊢(¬P∨Q). I don't see an obvious inference rule at this point, but we could show it by contradiction.
shareciteimprove this answer
edited Mar 20 '17 at 16:53
answered Mar 20 '17 at 16:10

You might also like